Evaluation of the interaction of ubiquitous systems: Applying the MALTU model and Extended Maltu in a IoT water device - Silva, Pedro Victor de Sousa; Cruz, Larah Virgínia Pedrosa Lima; Souza, Ruan Gabriel Lopes e; Souza, Anna Julia Abreu Lima de; Sampaio, Andréia Libório; Silva, Marcelo Martins da (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Ubiquitous systems integrate into people’s daily lives imperceptibly, making it crucial to evaluate these devices to understand users’ needs. This article aims to report the experience of evaluating a smart device using the HCI techniques MALTU and Extended MALTU. To evaluate the device in question, spontaneous user posts (SUPs) were manually and automatically extracted from social platforms, and after extraction, all SUPs were categorized. Using the MALTU method, 41 comments were analyzed, resulting in 38 criticisms (92.6%) and 5 compliments (12.1%). The comments revealed usability issues such as Effectiveness (46.3%), Efficiency (29.2%), Utility (26.8%), Memorability (4.8%), and Satisfaction (2.4%). The Extended MALTU method analyzed 237 comments, with 170 criticisms (63.9%) and 57 compliments (21.4%). The comments revealed aspects related to Context Sensitivity (18.5%), Invisibility (2.5%), Attention (17.5%), Calm (5.9%), Mobility (2.1%), and Synchronicity (53.5%). When observing the results, the MALTU and Extended MALTU models helped identify usability and user experience problems; however, one specifically helped to more explicitly identify issues related to quality criteria in intelligent systems. From the evaluation process using both methods, we highlight in the article some lessons learned and recommendations for evaluating ubiquitous systems.